Impact of the underground mining on aquifers: perspectives in the Colombian context (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
In this work the environmental impact of underground mining on water resources and its conceptual implications in Colombian are studied; in particular the implications of conceptual approaches to numerical modeling of the quantification of these impacts on water resources are subject to a comprehensive review. A model protocol is proposed to simulate the impact of water extraction from tunnels and geochemical changes on subsurface and surface water. This protocol is mainly focused on conceptual hydrological set ups that include the analysis of changes in groundwater flow paths, the induced connection of hydrogeological units previously disconnected and regional groundwater drawdown. The protocol proposed represents the starting point towards the construction of a decision support system based on the adequate quantification of the impacts that would allow us to design suitable monitoring and follow-up systems as well as mitigation and remediation alternatives.The implications of different conceptual models on numerical modeling are further studied using typical assumptions on theoretical approaches widely used in the Colombia context. The latter is performed by comparing a synthetic case of fractured media to a homogeneous porous media. Results showed the relevance of using a conceptual approach that accounts for a comprehensive geometrical characterization of the fractured system in order to simulate the actual response of the aquifer. Results also show important differences between the discrete fracture and the equivalent porous media approach that may affect the appropriate design of control and mitigation measures.
Keywords: hydrogeological conceptual approaches; underground mining; numerical modeling; enviromental impacts